Hard times? : demographic change and the 1930s depression in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in History at Massey University - Marsden, Lucy E (Massey University, 1991)
The 1930s depression is well established in both the historiography and the popular consciousness in New Zealand as a major event with wide-reaching consequences. In this thesis New Zealand demographic data relating to marriages, fertility and mortality are examined for evidence of interruptions that can be attributed to the effects of the economic downturn associated with the 1930s depression. The conclusion reached is that while some interruptions are discernible, they are essentially slight and of short duration. This raises the possibility that the depression did not in fact have a very severe impact in New Zealand. Another possibility is that the relationship between economic circumstances and demographic behaviour may no longer be close, an argument that would seem to be supported by the inconsistency of trends over time, and in other English-speaking countries studied. Data relating to the incomes of five groups are then examined. The evidence is of a wide diversity of financial experience during the depression, with a marked effect on many, particularly the least skilled, the owners of small farms and other small businesses, and those already towards the lower end of the economic scale. In addition, it is shown that the cuts in wage rates and pensions were in general not a major factor in reducing real incomes, which suggests the relative importance in this of unemployment. Statistics relating to unemployment are then analysed. They support the findings regarding income, since the least skilled were the worst affected. It is concluded that while the scale of unemployment in the 1930s was an anomaly in this country, the period of severe unemployment was relatively short compared with that experienced by some other countries. In respect of the groups most likely to suffer unemployment, the depression was an intensification of the normal situation rather than an anomaly. Some possible reasons are suggested for the lack of correlation between demographic and economic trends, and for the prevalence of the belief that the depression was a "community trauma" in this country.
Keywords: 1929 Depression; New Zealand; Social conditions; Population; 20th century history